Neurobiology of Alzheimer’s Disease: Integrated Molecular, Physiological, Anatomical, Biomarker, and Cognitive Dimensions - Raskin, Joel; Cummings, Jeffrey; Hardy, John; Schuh, Kory; A. Dean, Robert (Current Alzheimer Research, 2015)
Background: Alzheimer’s disease (AD), the most common form of dementia, is a progressive neurodegenerative disorder with interrelated molecular, physiological, anatomical, biomarker, and cognitive dimensions. Methods: This article reviews the biological changes (genetic, molecular, and cellular) underlying AD and their correlation with the clinical syndrome. Results: Dementia associated with AD is related to the aberrant production, processing, and clearance of beta-amyloid and tau. Beta-amyloid deposition in brain follows a distinct spatial progression starting in the basal neocortex, spreading throughout the hippocampus, and eventually spreading to the rest of the cortex. The spread of tau pathology through neural networks leads to a distinct and consistent spatial progression of neurofibrillary tangles, beginning in the transentorhinal and hippocampal region and spreading superolaterally to the primary areas of the neocortex. Synaptic dysfunction and cell death is shown by progressive loss of cerebral metabolic rate for glucose and progressive brain atrophy. Decreases in synapse number in the dentate gyrus of the hippocampus correlate with declining cognitive function. Amyloid changes are detectable in cerebrospinal fluid and with amyloid imaging up to 20 years prior to the onset of symptoms. Structural atrophy may be detectable via magnetic resonance imaging up to 10 years before clinical signs appear. Conclusion: This review highlights the progression of biological changes underlying AD and their association with the clinical syndrome. Many changes occur before overt symptoms are evident and biomarkers provide a means to detect AD pathology even in patients without symptoms.
Keywords: anatomical